Stubby the war dog : the true story of World War I 's bravest dog - Bausum, Ann (Washington, D.C. : National Geographic, 2014)
American soldier J. Robert Conroy befriended a stray dog with a stumpy tail while training to fight overseas in WWI. They bonded so closely that Conroy smuggled him to Europe, where Stubby accompanied Conroy's regiment on the Western Front, lending both his superior olfactory senses and amiable temperament to the war effort.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Includes bibliographical references (pages 66-68) and index.
Accelerated Reader
Description based on print version record.
Keywords: Stubby (Dog) -- Juvenile literature; Dogs -- War use -- United States -- Juvenile literature; World War, 1914-1918 -- United States -- Juvenile literature; United States. -- Army. -- Infantry Regiment, 102nd -- Mascots -- Juvenile literature; United States. -- Army. -- Infantry Regiment, 102nd.; Dogs -- War use; Mascots; Stubby (Dog); United States; 1914 - 1918; Electronic books- OSLIS; Juvenile works; Electronic books